(untitled) (Revista Iberoamericana de Bioética, 2025)
Bioethics education grapples with the challenge of elucidating key concepts related to endof- life issues—such as euthanasia and assisted suicide—due to their inherent ambiguity and the controversies that arise. The Critical Glossary on Bioethics and End of Life serves as an innovative educational resource, offering precise definitions and critical analyses of ethical and normative dimensions. Developed by an interdisciplinary team and validated through meticulous review, the tool enhances critical thinking, synthesis, and communication skills. This article outlines its development methodology, while emphasizing the importance of and the diffusion of this material in different forums, thereby enriching its content and broadening its impact. This type of tool not only improves bioethics teaching but also stirs more informed and pluralistic ethical and clinical debates.